Gender Difference in Food Choice and Eating Practice and Their Association with Health among Students of Kathmandu, Nepal - Maginsh Dahal; Alisha Basnet; Sudip Khanal; Kushalata Baral; Smriti Dhakal (Hindawi Limited, 2022)
Background. Our eating practice is generally based on the food we choose to eat. The selection of unhealthy food, high cost of healthy food items, and easy availability of fast food may have negative impact on our health and eating behaviour. This study aims to access the gender difference in food choice and eating practice and their association with health among students in Kathmandu, Nepal. Methods. A cross-sectional descriptive study was conducted among 385 randomly selected undergraduate BBA (Bachelor in Business Administration) students of Tribhuvan University in Kathmandu by using semistructured self-administered questionnaire. The questionnaire included sociodemographic characters, health status, behaviour factors, eating practice, and food choice which were measured using Food Choice Questionnaire (FCQ). The data was analysed in SPSS. Frequency, percentage, mean, and standard deviation were calculated, and chi-square test and logistic regression were used to measure the association between two variables. Results. The study is comprised of 50.4% female and 49.6% male with mean ages of 20.04 and 20.75, respectively. A gender difference was observed in food choice but no gender difference was observed in eating practice. There was no significant association of food choice and eating practice with health. However, food choice and eating practice showed an association with the current living status of the respondents. Sensory appeal and health were the most important food choice motives among males and females, respectively. Conclusion. The study concluded that no gender difference was observed in food choice. However, gender difference was observed in eating practice. There was no association of food choice and eating practice with health.